2010
DOI: 10.1071/ah09751
|View full text |Cite
|
Sign up to set email alerts
|

Rural health career pathways: research themes in recruitment and retention

Abstract: We identified four stages: (1) making career choices; (2) being attached to place; (3) taking up rural practice; and (4) remaining in rural practice. This is termed the 'rural pipeline'. However, as some stages of the 'rural pipeline' refer specifically to the medical profession, we propose an extension of the notion of the medical 'rural pipeline' to include other professions such as nursing, midwifery and allied health. CONCLUSIONS. Utilising the 'rural pipeline' as a template for medicine, nursing and allie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 42 publications
2
38
0
1
Order By: Relevance
“…From an initial pool of 517 publications, we selected a total of five review articles that met the inclusion criteria [24-28]. …”
Section: Resultsmentioning
confidence: 99%
“…From an initial pool of 517 publications, we selected a total of five review articles that met the inclusion criteria [24-28]. …”
Section: Resultsmentioning
confidence: 99%
“…Last but not least, the study adds to the accumulating evidence that rural background is the strongest predictor of health professionals choosing rural practice locations 46,47 . This study's findings, which revealed that NODIP graduates who lived in rural towns during their childhood or adolescence are more inclined to choose and intend to remain in rural practice, confirm the same is true of dietitians: those who come from rural backgrounds more often work rurally 48 .…”
mentioning
confidence: 95%
“…Greater organizational, regional, and country-related context-sensitivity is needed to determine effective recruitment and retention approaches [11, 13, 14]. In order to create such sensitivity to the needs of the nursing workforce in rural and remote contexts, where nurses are sometimes the only health care providers, more knowledge about that workforce, its diversity, and needs is urgently required.…”
Section: Introductionmentioning
confidence: 99%